Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.1 Inverse Functions - 6.1 Exercises - Page 407: 24


The inverse function is $$f^{-1}(x)=\frac{3x+1}{4-2x},\quad x\neq 2.$$

Work Step by Step

First, we have to exclude $2x+3=0\Rightarrow x=-\frac{3}{2}$ from the domain of the function because the denominator must be different than zero. That same value must be excluded from the range of the inverse function as well. Now, let $y=f(x)=\frac{4x-1}{2x+3}$ to find the inverse function we need to express $x$ in terms of $y$ and then we will have $x=f^{-1}(y).$ $$y=\frac{4x-1}{2x+3}\Rightarrow y(2x+3)=4x-1\Rightarrow 2xy+3y=4x-1\\ 4x-2xy=3y+1\Rightarrow x=\frac{3y+1}{4-2y},$$ so $$x=f^{-1}(y)=\frac{3y+1}{4-2y}.$$ Renaming $y$ back to $x$ we get $$f^{-1}(x)=\frac{3x+1}{4-2x}$$ where $x\neq 2$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.